Cellular Automata approach for parallel machine scheduling problem. (February 2016) - Kucharska, Edyta; Grobler-Dębska, Katarzyna; Rączka, Krzysztof; Dutkiewicz, Lidia
The aim of the paper is to present a new approach based on the Cellular Automata technique for a specific class of scheduling problems with parallel machines (in which some important parameter values cannot be determined a priori). The problem domain is represented by an asynchronous non-homogeneous cellular automaton. In addition, the division of the method into three levels is introduced. Inseparable use of simulation, optimization and result levels, is proposed. To illustrate our proposition, the optimization problem of drilling tunnels in a given area is considered. A number of simulation experiments were performed involving different instances of the problem and the results are presented and discussed in the paper.